America the beautiful: Missouri Missouri - Sanford, William R. (William Reynolds), 1927-; Green, Carl R. (Chicago : Childrens Press, 1990)
Introduces the geography, history, government, economy, industry, culture, historic sites, and famous people of the "Show me" state.
Includes index.
Keywords: Missouri; Missouri -- Juvenile literature